RISK MANAGEMENT ANALYSIS BASED ON ISO 31000: 2018 CASE STUDY AT ZAURA SUPERMARKETS IN EAST ACEH - Kamal Syafaqah, Cut; Ristati, Ristati (Journal of Accounting Research, Utility Finance and Digital Assets, 2022)
This study aims to find out how to analyze risk management based on ISO 31000:2018 in the Zaura Swalayan business. The data used in this study were structured and unstructured interviews. The method used in this study was carried out based on the ISO 31000:2018-based risk management process. The results showed thatThe risks faced by Zaura Swalayan are:bad credit,there is a damaged or defective product,accumulation of goods,wrong selling price,broken computer,the impact of the covid-19 pandemic,competition,unsatisfactory service,theft,natural disasters, andpower outage. The handling/management carried out has not been maximized due to the absence of a special team to handle/manage these risks. At Zaura Supermarketthere is no very high level of risk,there is only 1 risk with a high level of risk, there are 5 risks with a moderate level of risk, there are 5 risks with a low level of risk and there are 2 risks with a level of riskwhichvery low.